The English Proficiency of the Academics of the Teacher Training and Education Institutions - Ali Saukah (Universitas Negeri Malang, 2016)
The study is aimed at describing the general English proficiency level of the academics of Teacher Training and Education Institutions (LPTK's) as indicated by their TOEFL scores. Specifically, the study is focused on finding out whether there is any difference among the academics' English proficiencies when they are grouped in terms of the geographic regions of their institutions and their fields of study. This study is also intended to reveal any possible relationship between the academics' English proficiency and their age. The results indicate that the English proficiency of the academics on the average is far below the average of that of the international students. The academics in West Java are the highest in their English proficiency, and the English group, as expected, has the best English proficiency. In addition, there is a negative correlation between English proficiency and age